Impacts of Demography on E-Banking Transactions of Individual Customers at BIDV Bac Lieu - Pham, Phat Tien; Lam, Anh Thu (Tạp chí Khoa học HUFLIT, 2025)
The study investigates the impact of demographic factors on e-banking transactions of individual customers at BIDV Bac Lieu. Based on a literature review and available data, five demographic factors were identified. Daily transaction data from July 3 to August 31, 2024, provided by BIDV Bac Lieu, was analyzed to test the proposed model. The estimation results, obtained using the Ordinary Least Squares method, reveal that gender, age, occupation and income affect transaction volume, while gender, age, and income influence transaction value. Based on these findings, the study offers several policy recommendations to enhance e-banking transactions.